2008
DOI: 10.2514/1.27616
|View full text |Cite
|
Sign up to set email alerts
|

Improving Lunar Return Entry Range Capability Using Enhanced Skip Trajectory Guidance

Abstract: The impending development of NASA's Orion crew exploration vehicle will require a new entry guidance algorithm that provides sufficient performance to meet all requirements. This study examined the effects on entry footprints of enhancing the skip trajectory entry guidance used in the Apollo program. The skip trajectory entry guidance was modified to include a numerical predictor-corrector phase during the atmospheric skip portion of the entry trajectory. A 4-degree-of-freedom simulation was used to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…It is evident that many of the misses are tens to hundreds of kilometers from the intended landing site. This is a well-known limitation of the Apollo algorithm [24]. The Apollo algorithm calculates incorrect exit conditions for the upcontrol phase (the exit point of the skip).…”
Section: Results For Apollo Skip Entry Guidancementioning
confidence: 98%
See 3 more Smart Citations
“…It is evident that many of the misses are tens to hundreds of kilometers from the intended landing site. This is a well-known limitation of the Apollo algorithm [24]. The Apollo algorithm calculates incorrect exit conditions for the upcontrol phase (the exit point of the skip).…”
Section: Results For Apollo Skip Entry Guidancementioning
confidence: 98%
“…With modern Global Positioning System (GPS) data, as discussed in Ref. [24], greater knowledge of vehicle state information is expected. The same knowledge of vehicle state is permitted for the FNPEG algorithm to facilitate the comparison.…”
Section: Modifications For Current Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Both algorithms use a numerical predictorcorrector for the skip phase coupled with the Apollo ¦nal phase entry guidance. Putnam et al also presented a skip entry guidance by introducing a numerical predictorcorrector phase during the atmospheric skip portion with an Apollo guidance baseline algorithm [3]. Vernis et al reported a numerical predictorcorrector entry guidance that had been designed within the frame of the ESA-funded ¢Robust skip Entry£ program [6].…”
Section: Introductionmentioning
confidence: 99%